Generation of monoclonal antibodies to the anti-trypanosomal drug isometamidium - Peregrine, A.S.; Eisler, M.C.; Katende, J.; Flynn, J.N.; Gault, E.A.; Kinabo, L.D.B.; Holmes, P.H. (1994)
Mice were immunized with either an isometamidium-human serum albumin (HSA) conjugate or an isometamidium-porcine thyroglobulin conjugate (PTG). Thereafter, monoclonal antibodies (MAbs) IL-A 1001, IL-A 1002, IL-A 1003, 5F7.B7, and 5F7.C9 were generated and selected on the basis that they recognized conjugated and unconjugated isometamidium, but lacked cross-reactivity with the carrier molecules. All five MAbs were of the IgG1 isotype. Each of the five MAbs was assessed in a competitive ELISA for isometamidium; in each case, the minimum level of detection was approximately 10ng/ml. Each MAb exhibited approximately 0.1% cross-reactivity with the anti-trypanosomal compound diminazene. However, based on their cross-reactivity with the anti-trypanosomal compound homidium, the MAbs could be divided into two groups; IL-A 1001, IL-A 1002, and IL-A 1003, produced using an isometamidium-HSA conjugate as an immunogen, exhibited low levels of cross-reactivity (approximately 0.1%). In contrast, 5F7.B7 and 5F7.C9, produced using an isometamidium-PTG conjugate as an immunogen, exhibited high levels of cross-reactivity.